Calorimetric study and microstructure analysis of the order-disorder phase transformation in silicon steel built by SLM - Lemke, J.N.; Simonelli, M.; Garibaldi, M.; Ashcroft, I.; Hague, R.; Vedani, M.; Wildman, Ricky D.; Tuck, C. (Elsevier, 2017)
Innovative Additive Manufacturing (AM) technologies like Selective Laser Melting (SLM) could prove to be efficient for the processing of brittle silicon steel (Fe-Si) with high silicon content. This research elucidates the effects of heat-treatment on the microstructure of SLM-built high silicon steel, with particular emphasis on the formation of ordered phases, which are known to cause undesired material embrittlement.